A prospective phase II trial of EGCG in treatment of acute radiation-induced esophagitis for stage III lung cancer. Issue 3 (March 2015) - Zhao, Hanxi; Xie, Peng; Li, Xiaolin; Zhu, Wanqi; Sun, Xindong; Sun, Xiaorong; Chen, Xiaoting; Xing, Ligang; Yu, Jinming
Abstract Background Acute radiation-induced esophagitis (ARIE) is one of main toxicities complicated by thoracic radiotherapy, influencing patients' quality of life and radiotherapy proceeding seriously. It is difficult to be cured rapidly so far. Our phase I trial preliminarily showed that EGCG may be a promising strategy in the treatment of ARIE. Materials and methods We prospectively enrolled patients with stage III lung cancer from the Shandong Tumor Hospital & Institute in China from January 2013 to September 2014. All patients received concurrent or sequential chemo-radiotherapy, or radiotherapy only. EGCG was administrated once ARIE appeared. EGCG was given with the concentration of 440 μmol/L during radiotherapy and additionally two weeks after radiotherapy. RTOG score, dysphagia and pain related to esophagitis were recorded every week. Results Thirty-seven patients with stage IIIA and IIIB lung cancer were enrolled in this trial. In comparison to the original, the RTOG score in the 1st, 2nd, 3rd, 4th, 5th week after EGCG prescription and the 1st, 2nd week after radiotherapy decreased significantly (P = 0.002, 0.000, 0.000, 0.001, 0.102, 0.000, 0.000, respectively). The pain score of each week was significantly lower than the baseline (P = 0.000, 0.000, 0.000, 0.000, 0.006, 0.000, 0.000, respectively). Conclusion This trial confirmed that the oral administration of EGCG is an effective and safe method to deal with ARIE. A phase III randomized controlled trial is expected to further corroborate the consequence of EGCG in ARIE treatment.